Pengembangan Media Pembelajaran Interaktif Berbasis Quizizz Pada Materi Pelajaran Otomatisasi Tata Kelola Kepegawaian Kelas XI - Fadah Fenny Permataisari (Jurnal Syntax Admiration, 2024)
The purpose of this research is to develop interactive learning media based on wordwall in the subject of Personnel Governance Automation and to determine the feasibility of Quiziz-based learning media in the subject of Personnel Governance Automation class XI Office Management at SMK Satya Bhakti 2 Jakarta. The type of research used is research and development (RnD) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development method. This research took place at SMK Satya Bhakti 2 Jakarta which was carried out in June 2024. Data collection was conducted by means of interviews with teachers of SMK Satya Bhakti 2 Jakarta. The feasibility of learning media is assessed by media experts and material experts. Data analysis was carried out by qualitative and quantitative analysis. Based on the research that has been carried out by Quizizz-based interactive learning media that has been developed as a result of expert validation, it is known that interactive learning media using Quizizz in the subject of Personnel Governance Automation class XI is very feasible to use. The average result of media experts is 95% and material experts are 96%, so it is categorized as "very feasible" as an interactive learning media.